Kertvárosi tréfacsinálók és márkatudatos iskolások: A frankofón kölyökképregény - Maksa, Gyula (Studia Litteraria, 2019)
The study overviews the francophone versions of kid comics and focuses on works that are significant recipients of this genre tradition. The radical reformation of the francophone kid comics’ genre, which became popular since mid-20th century, happened in the 1990s, and can mostly be bound to those humorous album series that break away from the traditional idealized innocent depiction of child-life. Taking into account the experiences of the forming history of the kid comics’ genre the child-life depiction of other genres seem exciting to study. Especially the child-life representation of contemporary European graphic novels that centre on childhood, these account for an important part of the widely researched biographical graphic novels.